The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1371/journal.pgen.1000453
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Local Genome Sequence on Defining Heterochromatin Domains

Abstract: Characterizing how genomic sequence interacts with trans-acting regulatory factors to implement a program of gene expression in eukaryotic organisms is critical to understanding genome function. One means by which patterns of gene expression are achieved is through the differential packaging of DNA into distinct types of chromatin. While chromatin state exerts a major influence on gene expression, the extent to which cis-acting DNA sequences contribute to the specification of chromatin state remains incomplete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 86 publications
0
31
0
Order By: Relevance
“…3), embryos, and fly tissues (arms 2L and 3L, Supplemental Fig. 3) argues against a mechanism involving strict sequence-based boundary elements, as observed in S. pombe (Scott et al 2006;Wheeler et al 2009). We favor the hypothesis that border positions depend on the ''epigenetic balance'' between euchromatic and heterochromatic chromatin components, as suggested by studies of rearranged chromosomes (Ebert et al 2004;Rudolph et al 2007).…”
Section: Epigenomic Patterns Demonstrate Variable Positioning Of Hetementioning
confidence: 90%
“…3), embryos, and fly tissues (arms 2L and 3L, Supplemental Fig. 3) argues against a mechanism involving strict sequence-based boundary elements, as observed in S. pombe (Scott et al 2006;Wheeler et al 2009). We favor the hypothesis that border positions depend on the ''epigenetic balance'' between euchromatic and heterochromatic chromatin components, as suggested by studies of rearranged chromosomes (Ebert et al 2004;Rudolph et al 2007).…”
Section: Epigenomic Patterns Demonstrate Variable Positioning Of Hetementioning
confidence: 90%
“…This process, impacted by the chromosomal context [44], involves a complex interplay between histone-modifying activities and proteins that bind to modified histones [5]. Spreading of heterochromatin has been reported to require RNAi [45].…”
Section: Spreading and Maintenance Of Heterochromatinmentioning
confidence: 99%
“…Here, we identified an LTR at the border between these chromatin domains, and showed that LTR-containing DNA functions as a barrier-type insulator that can protect a transgene from negative chromosomal position effects. This LTR colocalizes with a peak of histone modification H3K4me2, suggesting that it may share with other barrier-type insulators the capacity to recruit histone modifying enzymes that can block the propagation of silent chromatin (1619). We suggest that by functioning in this way, this LTR helps to maintain the integrity of the E β -regulated chromatin domain in the murine Tcrb locus.…”
Section: Discussionmentioning
confidence: 96%
“…In vertebrates, enhancer-blocking is mediated by the DNA binding protein CTCF (CCCTC-binding protein), which is thought to function by promoting the formation of chromatin loops (1315). Several mechanisms have been proposed to explain barrier activity, but a common theme is the recruitment of histone modifying enzymes that deliver activating chromatin modifications which can interrupt the propagation of silent chromatin (1619). While transcriptional activity has been demonstrated for many yeast insulators with barrier function, transcription is not an absolute requirement for this function (2021).…”
Section: Introductionmentioning
confidence: 99%